THE DEVELOPMENT OF INTEGRATED SCIENCE INTERACTIVE E-MODULE BASED ON ETHNOSCIENCE FOR ENERGY IN THE LIVING SYSTEM LEARNING MATERIALS AS A LEARNING RESOURCES FOR 7th GRADER - Ramadhani, Rehani (Universe, 2024)
This research aims to produce a teaching material of an interactive e-module based on ethnoscience for energy in the living system that is valid and practical. The research uses Research and Development (R&D) with the ADDIE development model, but the research is only limited to the development stage due to the limited research time. The product of this research is designed using the application of Articulate Storyline 3. Based on the research that has been done, the data obtained from the validity and practicality test results. First, the results of the interactive e-module validity test by experts or lecturers obtained a kappa moment average of 0.92 with a very high validity category. Second, the results of the interactive e-module practicality test by the teacher are in the very practical category with a kappa moment average obtained of 0.96. Third, the results of the interactive e-module practicality test by students with a kappa moment average value of 0.93 are in the very practical category. Based on the data obtained, it can be seen that the integrated science interactive e-module based on ethnoscience of energy in living systems as a learning resource for 7th grade is valid and practical.